1975
DOI: 10.1002/j.2333-8504.1975.tb01071.x
|View full text |Cite
|
Sign up to set email alerts
|

Criterion Measures for Youth‐work Training Programs: The Development of Relevant Performance Dimensions

Abstract: An attempt to develop relevant criterion measures for work-training programs serving disadvantaged adolescents involved the longitudinal application of 32 trainee performance criteria at program completion and 40 longer-term outcome measures approximately six months following training. Factor analyses of those variables yielded four program completion (prOXimal) criterion dimensions of work motivation and planning ability, personal-social adjustments and training program competency. Post-program (distal) varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
1987
1987

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The issue of predicting the job performance of low-income workers has also been addressed by Freeberg (1976), although the primary intent of his study was to provide an empirical method for developing criteria for program evaluation and test validation. He found that measures taken immediately after program completion were significantly related to work-related variables measured six months later.…”
Section: Developmental View Of Vocational Maturitymentioning
confidence: 99%
“…The issue of predicting the job performance of low-income workers has also been addressed by Freeberg (1976), although the primary intent of his study was to provide an empirical method for developing criteria for program evaluation and test validation. He found that measures taken immediately after program completion were significantly related to work-related variables measured six months later.…”
Section: Developmental View Of Vocational Maturitymentioning
confidence: 99%